2015
DOI: 10.1080/15226514.2015.1045129
|View full text |Cite
|
Sign up to set email alerts
|

Phytoremediation of Metal Contaminated Soil Using Willow: Exploiting Plant-Associated Bacteria to Improve Biomass Production and Metal Uptake

Abstract: Short rotation coppice (SRC) of willow and poplar is proposed for economic valorization and concurrently as remediation strategy for metal contaminated land in northeast-Belgium. However, metal phytoextraction appears insufficient to effectuate rapid reduction of soil metal contents. To increase both biomass production and metal accumulation of SRC, two strategies are proposed: (i) in situ selection of the best performing clones and (ii) bioaugmentation of these clones with beneficial plant-associated bacteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 67 publications
0
23
0
Order By: Relevance
“…Recent studies have confirmed the potential of willows to survive in metal-enriched soils and their use in phytoremediation [7][8][9][10]. Although willows are not hyperaccumulator plants, their tolerance to HM toxicity, rapid growth and high biomass production makes them suitable for phytoremediation [8][9][10][11][12]. Willows are utilized in short rotation coppicing systems for both biofuel production and soil remediation purposes [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have confirmed the potential of willows to survive in metal-enriched soils and their use in phytoremediation [7][8][9][10]. Although willows are not hyperaccumulator plants, their tolerance to HM toxicity, rapid growth and high biomass production makes them suitable for phytoremediation [8][9][10][11][12]. Willows are utilized in short rotation coppicing systems for both biofuel production and soil remediation purposes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Willows are multipurpose trees [5] that have high biomass production, rapid regeneration, an extensive root system and tolerance to changed environmental conditions [6]. Recent studies have confirmed the potential of willows to survive in metal-enriched soils and their use in phytoremediation [7][8][9][10]. Although willows are not hyperaccumulator plants, their tolerance to HM toxicity, rapid growth and high biomass production makes them suitable for phytoremediation [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Plant growth promoting bacteria residing in the rhizosphere or phyllosphere of halophytes enhance plant growth through different mechanisms such as production of phytohormones (indole acetic acid, cytokinin), solubilization of minerals (P, Zn), nitrogen fixation and control of plant pathogens by production of siderophores and HCN [37,70,71]. Halophilic bacteria and archaea also play an important role in the bioremediation of contaminated soils by degradation of complex organic compounds and facilitating the process of phytoremediation [72,73]. Progress in sequencing technologies and metadata analysis showed that plant-microbe interactions are regulated by different mechanisms through a complex network of signaling events and consequently alleviating the salinity stress.…”
Section: Role Of Halophyte Microbiome In Salinity Tolerancementioning
confidence: 99%
“…83,84 Along with trees, recent reports suggest that hyperacculumators (plants that can accumulate high levels of toxins) and their associated microbes may play a key role in phytoremediation and can support organized endophytic communities. 1,5,12,45,64,85 Hyperaccumulators may be used to accumulate heavy metals often found in wastes and at contaminated sites such as As, Cu, Pb, Se, and Zn. 86,87 This is critical as metals are difficult to remove using traditional techniques and are often only controlled or immobilized.…”
Section: Candidates For Endophytic Phytoaugmentationmentioning
confidence: 99%
“…Methods of phytoremediation are thoroughly reviewed in Salt et al and Ali et al 1,5 Phytoremediation has been used to remediate numerous chemicals including metals, radionuclides, pesticides and herbicides, excessive nutrients, and organic pollutants. 1,[7][8][9][10][11][12] Depending on the location and desired treatment outcome, there are several types of phytoremediation planting schemes and applications that have been shown to be successful. The most common phytoremediation applications are riparian buffer strips, which consist of a strip of plantings along a wetland, stream, river, or lake, or a vegetation filter, which is used more commonly for managing municipal wastes and landfill leachates.…”
mentioning
confidence: 99%